Role of Zirconia in Oxide-Zeolite Composite for Thiolation of Methanol with Hydrogen Sulfide to Methanethiol - Tinglong Yang; Mengqin Yao; Jun Ma; Peng Chen; Tianxiang Zhao; Chunliang Yang; Fei Liu; Jianxin Cao (Nanomaterials, 2022)
In this paper, the molecular sieve NaZSM-5 was modified with zirconium dioxide (ZrO2) by a hydrothermal coating process and other methods. By comparing the effects of the crystal phase structure of ZrO2 and the compositing method on the physicochemical properties and catalytic performance of the obtained composites, the structure–performance relationship of these composite catalysts was revealed. The results indicate that in the hydrothermal system used for the preparation of NaZSM-5, Zr4+ is more likely to dissolve from m-ZrO2 than from t-ZrO2, which can subsequently enter the molecular sieve, causing a greater degree of desiliconization of the framework. The larger specific surface area (360 m2/g) and pore volume (0.52 cm3/g) of the m-ZrO2/NaZSM-5 composite catalyst increase the exposure of its abundant acidic (0.078 mmol/g) and basic (0.081 mmol/g) active centers compared with other composites. Therefore, this catalyst exhibits a shorter induction period and better catalytic performance. Furthermore, compared with the impregnation method and mechanochemical method, the hydrothermal coating method produces a greater variety of acid–base active centers in the composite catalyst due to the hydrothermal modifying effect.